Vertical variation of bacterial production and potential role in oxygen loss in the southern Bay of Bengal - Ye, Wenqi; Ma, Xiao; Liu, Chenggang; Ye, Ruijie; Priyadarshani, W. N. C.; Jayathilake, Ruchi; Weerakoon, Ashoka; Wimalasiri, Udeshika; Dissanayake, P. A. K. N.; Pathirana, Gayan; Iroshanie, R. G. A.; Zhu, Yuanli; et al. (Frontiers in Microbiology, 2023)
Marine environments wherein long-term microbial oxygen consumption exceeds oxygen replenishment can be associated with oxygen minimum zones (OMZ). The Bay of Bengal OMZ (BOB-OMZ) is one of the most intense OMZs globally. To assess the contribution of bacterial oxygen consumption to oxygen loss in BOB-OMZ, we measured bacterial production (BP), temperature, salinity, and dissolved oxygen (DO) in the whole water column. We then compared the estimated bacterial oxygen demand (BOD) with diapycnal oxygen supply (DOS) at depths of 50-200 m in the southern BOB in January 2020. The average BP was 3.53 ± 3.15 µmol C m −3 h −1 in the upper 200 m of four stations, which was lower than those reported in other tropical waters. The vertical distribution of BP differed between the open ocean and nearshore areas. In the open ocean, temperature and DO were the most important predictors for BP in the whole water column. In the nearshore areas, when DO increased sharply from the suboxic state, extremely high BP occurred at 200 m. The average estimated BOD/DOS could reach up to 153% at depths of 50-200 m, indicating advection and anticyclonic eddies manuscript submitted to frontiers in Microbiology probably are important DO replenishment pathways in the BOB.